Mind Mapping Learning Model to Improve Learning Outcomes of Circle Material - Safaten Sudoh; Sri Mahrani Hasibuan; Ahmad Nizar Rangkuti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is motivated by the fact that there are still many students who are less active in the learning process and still have difficulty answering the questions given by the teacher. The purpose of this study is to determine the application of the Mind Mapping learning model to improve students' Mathematics learning outcomes in class VIII-1 circle material of MTs Ja'fariyah Hutaibus. This research is a Classroom Action Research conducted using two Cycles, namely Cycle I with two Meetings and Cycle II with one Meeting. The instruments used are observations and tests in the form of test essays. The subject of this study was students in class VIII-1 MTs Ja'fariyah Hutaibus consisting of 27 students. The results of this study show that students’ learning outcomes are improving. It can be seen from the scores and activities of students starting from pretests with a percentage of student completion of 19% (5 out of 27 students) with a grade point average of 48.33, Cycle I: 1st Meeting , percentage of completeness of sisiwa 52% (14 out of 27 people) with an average score of 78.81, Cycle I: 2nd Meeting, percentage of student completion 74% (21 out of 27 people) with an average score of 86.11 and Cycle II, 1st Meeting, The percentage of student completion was 89% (24 out of 27 people) with an average score of 88.51. This shows that the application of the Mind Mapping learning model can improve mathematics learning outcomes for grade VIII-1 MTs Ja'fariyah Hutaibus students.